Analysis of Multiple Intelligence and Intelligence Quotient to Medical Record Officers Performance - Eka Wilda Faida; Anif Prasetyorini; Titin Wahyuni; Lilis Masyfufah; Puryanti (Indonesian Journal of Applied Research (IJAR), 2025)
Incomplete and inconsistent data recording, as well as low accuracy, were the main factors that reduced the quality of performance in health care facilities. Previous research showed that more than 50% of medical record officers competencies were categorized as low. Competence could impact hospital performance and quality. Competence could be measured by multiple intelligences and intellectual intelligence. It was important to carry out multiple intelligence and intelligence quotient analyses of the performance of medical record officers in recording patient medical data. The aim of the research was to assess the influence of multiple intelligence and intelligence quotient on the performance of officers in recording patient medical data. The method used was analytical observational research with a cross-sectional design. The purposive sampling technique involved 35 respondents. Data analysis was conducted using the Structural Equation Model with Partial Least Square. The influence of multiple intelligences on performance had a path coefficient value of -0.003 with a T-statistic value of 0.018 (< 1.96) and a P-value of 0.986, indicating no significant effect. There was a positive influence of intelligence quotient on performance with a path coefficient value of 0.745, a T-statistic value of 4.998 (> 1.96), and a P-value of 0.000. The strength of the influence of multiple intelligence and intelligence quotient on performance showed an R-square of 55%, which indicated a moderate influence.